PEMBERIAN PAKAN YANG DIFERMENTASIKAN DENGAN PROBIOTIK UNTUK PEMELIHARAAN IKAN LELE DUMBO (Clarias gariepinus) PADA TEKNOLOGI BIOFLOK feed fermented using probiotic for african catfish in biofloc technology - Triwahyu Yulianingrum; Niken Ayu Pamukas; Iskandar Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study aimed to determine the effect of feeding fermented with probiotic on, absolute body weight, absolute body length, specific growth rate, survival, feed efficiency and feed conversion rate of African catfish preserved biofloc techniques. The treatment in this study was the dose used for the fermentation of feed are 2 ml / kg (P1), 4 ml / kg (P2), 6 ml / kg (P3), and control (feed without fermented). Each treatment was repeated 3 times. 4-5 cm catfish were kept in the plastic tank with stocking density of 500 fish/m3 for 56 days. The fish are fed three times a day at satiation. The results showed fermented feed with probiotic on biofloc system affect absolute body weight, absolute length, specific growth rate, feed efficiency, and feed conversion rate of african catfish significantly, but did not affect survival rate. The best treatment was obtained from P3 which gives absolute body weight of 110.09 grams, absolute body length of 15.51 cm, specific growth rate of 8.03%, 92.62% survival rate, feed efficiency 117.22%, as well as feed conversion of 0.85.Keyword: Probiotic, catfish, biofloc technology